Compositional characteristics of kamafugites and carbonatites and their effects on performance as supplementary cementitious materials with portland cement in mortars - Buregyeya, Apollo Tumukwatirire (My University, 2022)
Kamafugites and carbonatites, unlike silica saturated volcanic materials, present a unique set of uncertainties on how compositional differences would affect their performance as supplementary cementitious materials (SCMs) in hydrating Portland cement. Having carbonate minerals as their primary composition, Kamafugites and carbonatites are undersaturated in silica and alumina composition compared to the more commonly studied mafic-felsic materials. The calcite bearing materials have potassic leaning alkalis with some deposits ultra-potassic. They are currently the only feasible source of SCMs in Uganda but no published work on their performance as SCMs existed at the time of this study and reporting. This thesis presents SCM properties of Kamafugites and carbonatites when blended with Portland cement pastes and mortars. Compositional characteristics of kamafugites and carbonatites and their effects on properties of fresh and hardened cement paste and mortar are reported. TGA, XRD, dilatometry, and Isothermal calorimetry instrumental techniques are applied together with other test procedures in characterizing kamafugites and carbonatites for composition properties, pozzolanic activity, strength development, chemical shrinkage, hydration kinetics and hydration phase assemblage when blended in Portland cement. Showing less pronounced pozzolanic activity, the kamafugites and carbonatites accelerate the hydration reaction of cement phases at early ages mainly due to the filler effect and the presence of calcite minerals and potassic leaning alkalis. The calcite bearing kamafugites and carbonatites have a time-dependent influence on the hydration products of the AFm phases in Portland cement paste with gypsum reactions ending at ettringite and the aluminate phases combining with carbonates to form carboaluminate hydration products. It is also observed that there is a loss of compressive strength of cement with 180 days’ strength becoming lower than the 90 days’ strength. The loss in strength is attributed to a combined effect of alkalis and carbonates which are observed to participate in the long term hydration reactions. Quantitative expressions based on thermogravimetric analysis results are applied in and proposed for characterisation of the degree of hydration, degree of pozzolanic activity, and the net SCM benefit of supplementary cementitious materials. The quantitative expressions are also applied in development of prediction models for compressive strength and chemical shrinkage of blended cement. The above findings are important in understanding how Portland cements that are blended with carbonatites and kamafugites are likely to perform in concrete. Considering that the materials are not addressed by existing standards, the experimental works presented in this thesis provide a basis for standardizing application of the kamafugites and carbonatites as SCMs in Portland cement concrete.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Civil and Environmental Engineering University of the Witwatersrand, Johannesburg, 2022